Teaching and Education manners in Islamic legacy (Journal Of Educational and Psychological Researches, 2015)
Learning education in the Islamic legacy vision considers a completed The Islamic learning education took its bases from origins of Quran and honored prophet Suna , and stressed on education child a good education and providing him with principles of religion and semantic moral values and Messenger (peace on him) considers the higher example for man in his moral, behavior and goodness and witness on this Higher God said(you had in God Messenger a good leadership for those were requesting God and last day and mentioned God a lot). Al- Ahzab Surah :21. learning education converts man from religion to another and from culture to another and teacher left his signs on the generation if he accept or refuse.